2017
DOI: 10.2174/1573403x13666170117125124
|View full text |Cite
|
Sign up to set email alerts
|

The Short and Long-Term Efficacy of Pulmonary Vein Isolation as a Sole Treatment Strategy for Paroxysmal Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Background:Pulmonary vein isolation (PVI) is an accepted treatment strategy for catheter ablation (CA) of paroxysmal atrial fibrillation (PAF). In this study, we aimed to assess the short, mid- and long-term outcome of PVI as a sole treatment strategy for PAF.Methods:Six bibliographic electronic databases were searched to identify all published relevant stud-ies until December 14, 2015. Search of the scientific literature was performed for studies describing outcomes with mean follow-up > 24 months after PAF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…PVI is associated with high rates of freedom from AF recurrence. The freedom rate from AF recurrence varies between 60 and 79% (Katritsis et al, 2008 ; Takigawa et al, 2015a ; Straube et al, 2016 ; Kis et al, 2017 ), 60 and 72% at 3 years (Vogt et al, 2013 ; Takigawa et al, 2015a ; Takarada et al, 2017 ) and decreases to 53–68% at 5 years (Neumann et al, 2013 ; Takigawa et al, 2015a , 2017 ; Kis et al, 2017 ). The long term freedom from AF may reach 77% (Vogt et al, 2013 ) after redo PVI.…”
Section: Implications For Af Ablationmentioning
confidence: 99%
“…PVI is associated with high rates of freedom from AF recurrence. The freedom rate from AF recurrence varies between 60 and 79% (Katritsis et al, 2008 ; Takigawa et al, 2015a ; Straube et al, 2016 ; Kis et al, 2017 ), 60 and 72% at 3 years (Vogt et al, 2013 ; Takigawa et al, 2015a ; Takarada et al, 2017 ) and decreases to 53–68% at 5 years (Neumann et al, 2013 ; Takigawa et al, 2015a , 2017 ; Kis et al, 2017 ). The long term freedom from AF may reach 77% (Vogt et al, 2013 ) after redo PVI.…”
Section: Implications For Af Ablationmentioning
confidence: 99%
“…Some of our patients were qualified for the next ablation, but it was not our point of interest in this study. Moreover, no data on silent AF were given by Scherr et al A meta-analysis of 13 different studies (1774 patients) [6] showed that the 12-month success rate of a single ablation procedure was 78%. However, different types of ablation procedures were used in these studies, and there were data on silent AF as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a review article by Kis et al on CA PVI treatment [ 14 ] showed a success rate of 78% (freedom from AF both on and off AADs) based on the majority of the included studies having 24-h Holter monitoring at different time intervals as a reflection of success. In our opinion, this would generally be insufficient to detect asymptomatic episodes of AF.…”
Section: Discussionmentioning
confidence: 99%